A novel nano-sized MoS2 decorated Bi2O3 heterojunction with enhanced photocatalytic performance for methylene blue and tetracycline degradation. Issue 13 (September 2019) - Ma, Zhanying; Hu, Linlin; Li, Xiaobo; Deng, Lingjuan; Fan, Guang; He, Yangqing
Abstract: In this paper, MoS2 was used as a band-suitable semiconductor to construct the Bi2 O3 /MoS2 heterostructured photocatalysts for the first time via a deposition-hydrothermal method. The XRD, SEM and HRTEM analysis indicated that the surface of Bi2 O3 was decorated with MoS2 nanoparticles and Bi2 O3 /MoS2 heterojunctions were formed. The performances on photocatalytic degradation of methylene blue (MB) and tetracycline (TC) were evaluated under visible light irradiation. The results demonstrated that the Bi2 O3 /MoS2 heterojunctions displayed remarkably improved photocatalytic activity for both MB and TC degradation, compared to the base material (Bi2 O3 ). Specifically, as the molar ratio of MoS2 was 23.81%, the obtained Bi2 O3 /MoS2 -23.81 heterojunctions exhibited promising photocatalytic activities, and approximately 100% MB and 97% TC were degraded within 100 min, respectively. The superior photocatalytic activity was mainly attributed to its large surface area, high visible-light harvesting and the efficient separation of photogenerated electrons and holes caused by the unique heterojunction architecture. Notably, the Bi2 O3 /MoS2 heterojunctions showed remarkable stability in recycling photocatatlytic experiments. The active species trapping and terephthalic acid (TA) fluorescence experiments indicated that the OH was the major reactive oxidizing species for MB degradation. Furthermore, the intermediates were detected by UPLC-MS spectrometry and the possible degradation pathways for MB and TC were proposed. Finally, a possible reaction mechanism of Bi2 O3 /MoS2 heterojunctions for the photodegradation MB was also proposed. This interesting interfacial architecture strategy will provide useful insights for designing and fabricating new class of binary heterojunctions with high-efficient photocatalytic activity towards practical application. Graphical abstract: A highly efficient visible-light responsive photocatalyst Bi2 O3 /MoS2 heterojunctions was prepared for the organic dyes and antibiotic pollutants elimination.Image 1 Highlights: Bi2 O3 /MoS2 heterojunction was prepared by deposition-hydrothermal method. Bi2 O3 /MoS2 -23.81 exhibited enhanced photocatalytic activity than that of pure Bi2 O3 . The electrons transfer and visible-light harvesting effects were obviously improved. The ⋅OH was the main oxidative species of Bi2 O3 /MoS2 -23.81 for the MB decomposition.